Association between gut microbiota and endometriosis: a two-sample Mendelian randomization study - Ji, Xuan; Yang, Qi; Zhu, Xiu-Lin; Xu, Li; Guo, Jie-Ying; Rong, Yan; Cai, Yun-Lang (Frontiers in Microbiology, 2023)
Background: Recent studies have shown that an imbalance in gut microbiota (GM) may not always be associated with endometriosis (EMS). To investigate this further, we conducted a two-sample Mendelian randomization study. Methods: MR analysis was performed on genome-wide association study (GWAS) summary statistics of GM and EMS. Specifically, the MiBioGen microbiota GWAS (N = 18,340) was used as exposure. The FinnGen study GWAS (8,288 EMS cases and 68,969 controls) was used as outcome. We primarily used the inverse variance weighted (IVW) method to analyze the correlation and conducted a sensitivity analysis to verify its reliability. Results: (1) MR analysis: The results of the IVW method confirmed that a total of 8 GM taxa were related to the risk of EMS. Class-Melainabacteria (p=0.036), family-Ruminococcaceae (p=0.037), and genus-Eubacteriumruminantium (p=0.015) had a protective effect on EMS, whereas order-Bacillales (p=0.046), family-Prevotellaceae (p=0.027), genus-Anaerotruncus (p=0.025), genus-Olsenella (p=0.036) and genus-RuminococcaceaeUCG002 (p=0.035) could increase the risk of EMS. (2) Sensitivity analysis: Cochrane’s Q test (P>0.05), MR-Egger intercept method(P>0.05), and leave-one-out method confirmed the robustness of MR results. Conclusion: This study performed a MR analysis on two large national databases and identified the association between 8 GM taxa and EMS. These taxa could potentially be utilized for indirectly diagnosing EMS and could lead to novel perspectives in research regarding the pathogenesis, diagnosis, and treatment of EMS.